Implementation Of Law Number 22 Of 2022 On Corrections In Protecting The Rights Of Female Prisoners - Rozali, M. Iqbal; Fahrian, Yudi; Yusi, Suryani (Fakultas Hukum Dehasen, 2025)
This study is entitled “Implementing Law Number 22 of 2022 on Corrections in the Protection of Women Prisoners' Rights” The focus of this study is the fulfillment of the rights of women prisoners who have biological, psychological, and social needs that differ from those of male prisoners, thus requiring special protection. Although Law No. 22 of 2022 and Government Regulation No. 32 of 1999 regulate the rights of inmates, practices in the field show many obstacles. The National Human Rights Commission report, for example, reveals that a number of women's correctional institutions in various regions do not provide psychological services, which is contrary to the provisions of the law. This study uses a normative legal approach with regulatory analysis, legal documents, and case studies to assess the implementation of Article 9 of Law No. 22/2022 in the rehabilitation of female prisoners. The results of the study show a discrepancy between progressive legal norms and practices in the field. Obstacles mainly arise from structural factors, resource constraints, and a lack of norms relevant to the specific needs of women. This study concludes that improvements in normative and structural aspects, supported by political support, resource distribution, and cross-party collaboration, are urgently needed to build a gender-sensitive correctional system that truly protects the rights of female prisoners.